Faktor-faktor yang mempengaruhi komitmen guru-guru sekolah rendah terhadap organisasi - Abdul Manaf, Bin Musa (1998)
The objectives of this study is to identify; a) the differences of organizational commitment among the teacher based on demographic factors, b) the relationship between job satisfaction and organizational commitment, c) the relationship between organizational climate and organizational commitment and d) the influence of independent variables on organizational commitment. The sample consists of 68 and 119 male and female teachers. They were selected by a random sampling method from nine different primary schools which are located in the Seberang Prai Selatan District, Pulau Pinang.